Standard Japanese Equivalents of Hakata Dialects in Movie Hanachan no Misoshiru - Sri Sundoro Ari, Murni; Aryanto, Bayu (Japanology: The Journal of Japanese Studies, 2024)
This study examines the comparisons of standard Japanese and Hakata dialects used in the movie Hanachan no Misoshiru. It aims to identify and analyze the linguistic forms of Hakata dialects and understand the differences in meaning and usage compared to standard Japanese. The design used in this research is a descriptive qualitative approach, and the data is collected through observation of dialog in the film. The data collected was then classified based on word class groups. The results show that the dialectal variety in jodoushi is found in verb patterns (-tou), which are comparable to standard Japanese in the form of sounds (chouon or long vowel sounds), and abbreviation of phonemes. The word classification in the form of keiyoushi or adjectives is found in the form of additional patterns of the final word (-ka), which undergoes word formation, namely the omission of sounds and the addition of phonemes.